UMKM berbasis teknologi desa kertawinangun Kecamatan Cidahu Kabupaten Kuningan - Wachjuni Wachjuni; Januar Habibi Masyar; Winda Oktaviani (IKIP SILIWANGI, 2023)
KertawinangunVillageisadevelopingvillagewhosemainrawmaterialsarericeandcassava.KertawinangunVillageisfamousasthecenterofKuningancuisinesuchasgemblong,variouschips,cirengandregginang.However,althoughthisisthecenterofKuninganspecialties,manyothervillagesinKuninganprovinceproducethesameKuninganspecialties,sothemarketdemandtendstodecreaseratherthanincreasefromtimetotime.NotethatthereisTheresultsofaninitialsurveyconductedshowedthatthedeclinethatoccurredwascausedbyanumberoffactors,includinghisMSMEswhowerenotusingtechnologyasamarketingmedium.Asaresult,thetargetmarketisstilllimited.Theproductpackagingisstillverysimple,sotheproductiseasytodamage,andtherearefewproductvariations.ThemethodologyforimplementingthiscommunityserviceistheParticipatoryRuralAppraisal(PRA)approach.Thefirsttrainingexerciseistheuseoftechnologyformarketingactivities.Asaresult,hisMSMEsinsomevillagesselltheirproductstoe-commerceshoppers.ThesecondtrainingisProductInnovationTraining.Theresultismoreappealingpackagingdesignandarangeofnewflavors. KertawinangunVillageisadevelopingvillagewhosemainrawmaterialsarericeandcassava.KertawinangunVillageisfamousasthecenterofKuningancuisinesuchasgemblong,variouschips,cirengandregginang.However,althoughthisisthecenterofKuninganspecialties,manyothervillagesinKuninganprovinceproducethesameKuninganspecialties,sothemarketdemandtendstodecreaseratherthanincreasefromtimetotime.NotethatthereisTheresultsofaninitialsurveyconductedshowedthatthedeclinethatoccurredwascausedbyanumberoffactors,includinghisMSMEswhowerenotusingtechnologyasamarketingmedium.Asaresult,thetargetmarketisstilllimited.Theproductpackagingisstillverysimple,sotheproductiseasytodamage,andtherearefewproductvariations.ThemethodologyforimplementingthiscommunityserviceistheParticipatoryRuralAppraisal(PRA)approach.Thefirsttrainingexerciseistheuseoftechnologyformarketingactivities.Asaresult,hisMSMEsinsomevillagesselltheirproductstoe-commerceshoppers.ThesecondtrainingisProductInnovationTraining.Theresultismoreappealingpackagingdesignandarangeofnewflavors.